Adapting the CACAO model to support higher education STEM teaching reform - Karen Viskupic; Brittnee Earl; Susan E. Shadle (SpringerOpen, 2022)
Abstract Background Efforts to achieve improved student outcomes in STEM are critically reliant on the success of reform efforts associated with teaching and learning. Reform efforts include the transformation of course-based practices, community values, and the institutional policies and structures associated with teaching and learning in higher education. Enacting change is a complex process that can be guided by change theories that describe how and why a desired change takes place. We analyzed the utility of a theory-based change model applied in a higher education setting. Our results provide guidance for change efforts at other institutions. Results Use of the CACAO model to guide the transformation of STEM instruction at a large public university resulted in changes to faculty teaching practices and department culture consistent with the vision defined for the project. Such changes varied across STEM departments in accordance with the emergent nature of project activities at the department level. Our application of the CACAO model demonstrates the importance of (1) creating a vision statement (statement of desired change or end-state); (2) attending to different levels of the organization (e.g., individuals, departments, and colleges); (3) working with change agents who are situated to be effective at different organizational levels; and (4) employing strategies to meet the needs and interests of faculty at different stages of adoption with respect to the desired change. Conclusion Our work, which demonstrates the utility of the CACAO model for change and captures its key elements in a matrix, provides a potential foundation for others considering how to frame and study change efforts. It reinforces the value of using change theories to inform change efforts and creates a structure that others can build on and modify, either by applying our CACAO matrix in their own setting or by using the matrix to identify elements that connect to other change theories. We contribute to the growing body of literature which seeks to understand how change theories can be useful and generalizable beyond a single project.